Witch hat atelier. Volume 9 - Shirahama, Kamome (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2022)
"With their magic contraptions in hand, Coco and her friends head to Ezrest for the annual festival, Silver Eve! The cobblestone streets of the crown city are lined with vibrant tents, and visitors from across the land partake in reunions and greetings anew. Here, witches, royals, the Knights Moralis, and even the Three Wise converge-each party carrying with them their private motivations and powerful histories. However, the bright lights and merriment lure in the uninvited as well ..."--